2021
DOI: 10.1007/s00217-020-03672-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orange-fleshed sweet potato flour particle size and degree of wheat flour substitution on physical, nutritional, textural and sensory properties of cookies

Abstract: Orange-fleshed sweet potato (OFSP) flour is rich in health-promoting compounds that can improve the nutritional benefits of baked products when blended with wheat flour. However, the flour particle size and blend proportion may affect the quality properties and consumer acceptability of bakery products. This study investigated the effect of flour particle sizes and blend proportions on the physical, nutritional, textural and sensory properties of peeled and unpeeled OFSP composite flour cookies. Peeled and unp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Thus, the highest ash content was observed for composite flour cupcake (1.98±0.03%) and cookies (1.71±0.05%) made from 50% of OFSP flour and the lowest was for the controls. The same trend was recorded in the ash content of the composite cakes and cookies made with wheat-OFSP flour reported by [40], [41]. It can be concluded that substitution of wheat flour with OFSP flour in the blends could enhance the mineral intake of consumers of the final composite products developed for proper growth and development especially for the children.…”
Section: Proximate Composition Of the Compsite Ofsp Flour Baked Productssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the highest ash content was observed for composite flour cupcake (1.98±0.03%) and cookies (1.71±0.05%) made from 50% of OFSP flour and the lowest was for the controls. The same trend was recorded in the ash content of the composite cakes and cookies made with wheat-OFSP flour reported by [40], [41]. It can be concluded that substitution of wheat flour with OFSP flour in the blends could enhance the mineral intake of consumers of the final composite products developed for proper growth and development especially for the children.…”
Section: Proximate Composition Of the Compsite Ofsp Flour Baked Productssupporting
confidence: 83%
“…Cupcakes supplemented with 50% OFSP flour recorded high score for all the three cultivars. This result may be attributed to natural sweet taste of OFSP flour that contributes to increase preference of panelists, as mentioned by [41]. However, the scores of texture and mouthfeel which reflect softness and chewiness of cupcakes decreased with addition of OFSP flour as shown in Table 4.…”
Section: Sensory Evaluation Of the Of The Composite Ofsp Flour Baked Productsmentioning
confidence: 90%
“…The higher vitamin C in SAPO4 and SAPO5 could be due to the increased amount of orange‐fleshed sweet potato flour in its formulation. Besides dietary fiber and essential minerals, orange‐fleshed sweet potato is a rich source of vitamin C in the form of ascorbic acid (Korese et al., 2021; Van, 2000). Specifically, vitamin C is a water‐soluble micronutrient that plays a vital role in an infant's physiological functions such as facilitating collagen production, maintaining a healthy immune system, and enhancing iron absorption (Hill, 2020; Ofoedu, Iwouno, et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, besides the proportions of soybean and pumpkin seeds used in the formulation, the increased amount of orange‐fleshed sweet potato could also influence the higher vitamin A content in SAPO4 and SAPO5. Previous studies have shown that orange‐fleshed sweet potato (OFSP) is a rich source of vitamin A in the form of β‐carotene (Burri, 2011; Korese et al., 2021; Van, 2000). This corroborates the findings of Waized et al.…”
Section: Resultsmentioning
confidence: 99%
“…Для підвищення пружності та стабілізації клітинної структури проводиться охолодження обробленого сировинного матеріалу шляхом промивання у воді. Одночасно з цим із поверхні змивається плівка, утворена залишками зруйнованих крохмальних зернин, які уповільнюють видалення вологи під час сушіння 19 .…”
Section: дослідження процесів тепловологої обробки та конвективного зневоднення коренеплодів бататуunclassified